(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
A version of the talk delivered at the University of Hullon 15 November 2000. With her husband, George Hartley, Jean founded The MarvellPress, which published Larkin’s first mature poetry collection, The LessDeceived, in 1955.